The principles of witness immunity - Shair Mohamed, Mohd. Akram (The Malaysian Current Law Journal Sdn Bhd, 2015)
It is an ancient principle of law, settled for generations that witnesses enjoy absolute immunity from actions being brought against them in respect of any evidence they may give in a court of justice. This immunity also covers certain pre-trial actions intimately connected with the conduct of the case in court. The immunity is granted to stop matters from being litigated again and again by the disgruntled parties, to protect the witnesses themselves from suits stemming from the evidence they are to give, and the need encourage witnesses to come forward and say what they have to in court. However such immunity needs to be checked against a broad view of the public interest. the general principle does not preclude prosecutions for prejury, preventing the courts of justice, for contempt of court, liability for malicious prosecution or misfeasance in public office